TRADING PARTICIPANTS CONCENTRATION ANALYSIS, AS A SELECTION METHOD OF SMALL AND MEDIUM CAPITALIZATION FOR INVESTORS PORTFOLIOS - A. Gulyatkin (Вестник университета)
The article describes securities selection methods at formation of an investor’s portfolio comprised of small and medium capitalization. The author examines a liquidity risk of the stocks, by exploring the relationship between supply and demand. In the paper are also discovered peculiarities of the analysis based on financial turnover and auction participants concentration. Being based on the theory of market participants cooperation as well as on personal experience, the author supplements the described analysis tools by recommendations that improve results of securities selection.